VISEGRAD SPEED: IS IT FAST ENOUGH? - Kreckova, Zuzana (European Scientific Journal, ESJ, 2014)
Visegrad countries are facing similar issues related to underrepresentation of women in the corporate decision making positions. Female population outnumbers the male one in the tertiary education attainment. The employment level of women is also high across all four counties. However, men outnumber women in the decision making positions at large corporations. Three out of four Visegrad countries did not adopt any measure to improve the situation in balancing the gender representation at boards. The article introduces outlook based on the model of organic growth. The results are not positive enough to let the situation as it is now. So, the situation calls for interventions.